Prominent need to increase the level of education and awareness in the field of terrorist activities - Halitovich Tukhvatullin, Airat (2021)
The relevance of the problem under study stems from the fact that the practice of terrorism is one of the main challenges of contemporary world politics, affecting various regions of our planet. In this regard, the study of this phenomenon within a particular region deserves special attention, Northern Ireland in this case. The practice of terrorism there has been a destabilising challenge almost throughout the twentieth century and is associated with unresolved interethnic and interreligious problems. The aim of the paper is to identify factors in the emergence, spread and de-escalation of political violence in Northern Ireland in a historical retrospective. The main approaches to the study of the problem in question are historical and analytical methods. The study shows the main reasons for the emergence and escalation of political violence and terrorism in Northern Ireland and indicates the main measures to find compromise in a multi-confessional and multi-ethnic society, which may be a model for the resolution of similar conflicts in other regions of the modern world. The materials of the paper can help to study the specifics of regional terrorism, to identify the main factors that allow reducing the level of social conflict, and to understand similar phenomena in other regions (the Balkan Peninsula, the Middle East, etc.). Moreover, it reveals the needs to make the awareness of the educated class of the society.